2021
DOI: 10.17516/1997-1370-0723
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationship Between Uncertainty Tolerance and Hardiness in Adolescents

Abstract: Objective – identify the relationship between the phenomena of uncertainty tolerance and hardiness in adolescents. Uncertainty tolerance (UT) is understood as a personality trait that manifests itself in an ability to accept uncertainty and act confidently in unstable situations. Adolescence is characterized as a period of instability. It is thus assumed that uncertainty tolerance is a significant parameter in the structure of adolescents’ hardiness. The research was designed to identify the relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 9 publications
0
10
0
3
Order By: Relevance
“…The study's findings indicated that undergraduate students' psychological hardiness was below average. Andronnikova ( 2021 ) evaluated the relationship between uncertainty tolerance and hardiness in adolescents and found that adolescents demonstrated average psychological hardiness. Qaisy ( 2016 ) assessed the psychological hardiness of Jordanian university students, and the finding indicated that the students' hardiness levels were moderate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study's findings indicated that undergraduate students' psychological hardiness was below average. Andronnikova ( 2021 ) evaluated the relationship between uncertainty tolerance and hardiness in adolescents and found that adolescents demonstrated average psychological hardiness. Qaisy ( 2016 ) assessed the psychological hardiness of Jordanian university students, and the finding indicated that the students' hardiness levels were moderate.…”
Section: Discussionmentioning
confidence: 99%
“…Hardiness is often essential for individuals' adaptation and development in challenging and unpredictable environments and psychological well‐being (Andronnikova, 2021 ). Several studies indicated that intolerance of uncertainty impacted psychological well‐being.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of human behaviour in uncertainty is presently an urgent problem, because people do not know how to behave in stressful situations (Andronnikova, 2021;Kocheulova, 2018;Tyutelova et al, 2019;Veresov, 2018). In the present study, the example of such a situation is the presence of children and adolescents on a remote island.…”
Section: Problem Statementmentioning
confidence: 99%
“…Исследования показывают, что жизнестойкость по-разному проявляет себя у подростков с различным уровнем агрессивности [5], уровень жизнестойкости связан с аутодеструктивным поведением подростков [6], уровнем толерантности к неопределённости [7], отношением к курению (выше жизнестойкость -хуже относятся к курению) [8], а также с предпочтением у подростков различных копинг-стратегий [9]. Так, например, Е. В. Евсеенкова и Ю. В. Борисенко показали, что компоненты жизнестойкости положительно коррелируют с уровнем активности, спокойствия, удовлетворённости и отрицательно -с уровнем депрессии и безнадёжности [6].…”
Section: Introductionunclassified